a) \(\left(1+x^2\right)^2-4x\left(1-x^2\right)\)
\(=\left(1+x^2\right)\left(1+x^2-4x\right)\)
b) \(\left(x^2-8\right)^2-36\)
\(=\left(x^2-8-6\right)\left(x^2-8+6\right)\)
\(=\left(x^2-14\right)\left(x^2-2\right)\)
\(a,\left(1+x^2\right)^2-4x\left(1-x^2\right)\)
=\(x^4+2x^2+1-4x+4x^3\)
=\(x^4+4x^3+2x^2-4x+1\)
=\(\left(x^4+2x^3\right)+\left(2x^3+4x^2\right)-\left(2x^2+4x\right)+1\)
=\(\left(x^3+2x^2-2\right)\left(x+2\right)\)+1
b,\(\left(x^2-8\right)^2-36\)
=\(\left(x^2-8-6\right)\left(x^2-8+6\right)=\left(x^2-14\right)\left(x^2+2\right)\)(trừ 36 nhé)